Nutrient intakes and impact of fortified breakfast cereals in schoolchildren. Issue 6 (December 1996) - McNulty, H; Eaton-Evans, J; Cran, G; Woulahan, G; Boreham, C; Savage, J M; Fletcher, R; Strain, J J
Abstract : OBJECTIVE: To report micronutrient intakes in Northern Ireland schoolchildren, and to establish the contribution of fortified breakfast cereal to overall nutrient intakes and achievement of current dietary recommendations. DESIGN: Analysis of dietary intakes and physical characteristics of participants in a randomly selected 2% population sample of 1015 schoolchildren aged 12 and 15 years in Northern Ireland during the 1990/1 school year. MAIN OUTCOME MEASURES: Dietary intakes, physical characteristics, and their association with consumption of fortified breakfast cereal. RESULTS: Mean micronutrient intakes were generally adequate with the exception of low intakes of folate (boys and girls) and iron (girls). Fortified breakfast cereals, consumed by a high proportion (94% boys; 83% girls) of the sample, were associated with higher daily intakes of most micronutrients and fibre and with a macronutrient profile consistent with current nutritional recommendations. Appreciable proportions of subjects who did not consume fortified breakfast cereals had daily intakes that fell below the lower reference nutrient intake for riboflavin, niacin, folate, vitamin B-12, and iron (girls). CONCLUSIONS: The results demonstrate the potential of fortification in contributing to micronutrient intakes of schoolchildren, particularly where requirements are high, or for those on marginal diets of low nutritional quality.